The Impact of International Trade on Gender Equality - Swamy, Gurushri (World Bank, Washington, DC, 2012)
Does trade improve prospects for women's employment and promote greater gender equality in wages? Trade creates or expands some activities and destroys or diminishes others. If an individual works in an expanding sector or is able to switch to one, she or he is likely to benefit. Evidence shows that trade tends to increase the availability of wage jobs for women, particularly in export sectors. But certain factors-such as discrimination, lower skills, and gender inequalities in access to resources-may impede women's ability to benefit from trade expansion. Some of these factors may be especially prevalent among female farmers in Sub-Saharan Africa.